Intergenerational digital storytelling: four racconti of a new approach - Luca Botturi; Isabella Rega (Pensa MultiMedia, 2014)
Digital storytelling has been slowly penetrating the world of education and social development since a while. Intergenerational learning seems a promising and somehow natural domain for digital storytelling, as it offers a perfect venue to bring together memory and wisdom with digital media skills and vibrant communication. This paper presents the efforts made by Associazione seed to transfer digital storytelling to intergenerational learning, based on its previous work with the Digital Storytelling for Development model in many fields.